Exploring the Predictive Value of Inflammatory Biomarkers in COVID-19 Patients: A Prospective Cohort Study in Malang, Indonesia - Agustin Iskandar; Hambiah Hari Oki; Catur Suci Sutrisnani; Novi Khila Firani; Nur Samsu; Agustina Tri Endharti; Edi Widjajanto (Universitas Gadjah Mada, 2023)
The objective of this study was to assess the predictive value of inflammatory biomarkers in COVID-19 patients, namely the CRP/albumin ratio (CAR), interleukin 6 (IL-6), IL-6/lymphocyte ratio (IL-6/LY), and neutrophil/lymphocyte ratio (NLR). A prospective cohort study was conducted between January to June 2021 at Dr. Saiful Anwar General Hospital, Malang, East Java, Indonesia. CRP and albumin levels were measured using COBAS C6000. IL-6 was measured using the enzymatic chemiluminescence immunoassay (ECLIA) method and NLR was calculated based on flow cytometry evaluation of neutrophil and lymphocyte. Patient outcomes were obtained from medical records. Out of the 102 COVID-19 patients, 60 were non-survivors. The findings revealed that the area under the receiver (AUC) for CAR, IL-6, IL-6/LY, and NLR were 0.71, 0.77, 0.75, and 0.65, respectively. Kaplan-Meier curve analysis demonstrated significant differences between the groups stratified by these cut-off values. Notably, CAR and IL-6 exhibited the most accurate predictive values for mortality in COVID-19 patients. These findings suggest that CAR and IL-6 may serve as valuable biomarkers for predicting mortality in COVID-19 patients. Importantly, CAR offers an advantage over IL-6 as it is relatively more affordable, making it a viable option even if COVID-19 becomes endemic.